Estimation of lateral force contribution of boundary elements in steel plate shear wall systems. (29th November 2016) - Verma, Abhishek; Sahoo, Dipti Ranjan
Summary: Steel plate shear walls (SPSWs) are used as lateral force‐resisting systems in new and retrofitted structures in high‐seismic regions. Various international codes recommend the design of SPSWs assuming the entire lateral load to be resisted by the infill plates. Such a design procedure results in significant overstrength leading to uneconomical and inefficient use of materials. This study is focused on the estimation of contribution of boundary elements in resisting the lateral force considering their interaction with the web plates of SPSW systems. Initially, the relative contribution of web plates and boundary frames is computed for a single‐bay single‐story frame with varying rigidity and end connections of boundary elements. Nonlinear static analyses are carried out for the analytical models in OpenSees platform to quantify this contribution. Later, this study is extended to the code‐based designed three‐story, six‐story, and nine‐story SPSWs of varying aspect ratios. Based on the results obtained, a new design procedure is proposed taking the lateral strengths of the boundary frames into account. Nonlinear time‐history analyses are conducted for 40 recorded ground motions representing the design basis earthquake and maximum considered earthquake hazard levels to compare the interstory and residual drift response and yield mechanisms of SPSWs designed as per current practice and the proposed methodology. Finally, an expression has been proposed to predict the lateral force contribution of the infill plate and the boundary frame of SPSWs. Copyright © 2016 John Wiley & Sons, Ltd.